The system of reports and financial charges related to the use of the environment: Some proposals for improvement - Mariusz Rogulski (Economic and Environmental Studies (E&ES), 2013)
This article presents an analysis of the Polish system of environmental reporting and financial charges. It describes the main forms of information reporting and payment obligations in Poland as determined by law. Next, a brief examination of the revenue from these sources is presented and some practical aspects related to the functioning of the system are discussed. The article highlights the multiplicity of reporting requirements and corresponding huge burdens for businesses and public administration. The goal of the paper is to present several proposals for the improvement of the system through the use of, inter alia, new technologies to facilitate the execution of reporting by entities benefiting from the environment or entail the centralization of data on all entities using the environment.
Keywords: 330; entities using the environment; environmental reports; environmental taxes